2013
DOI: 10.1021/cn4000555
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde Cross-Linked Glutamate Oxidase Coated Microelectrode Arrays: Selectivity and Resting Levels of Glutamate in the CNS

Abstract: Glutaraldehyde is widely used as a cross-linking agent for enzyme immobilization onto microelectrodes. Recent studies and prior reports indicate changes in enzyme activity and selectivity with certain glutaraldehyde cross-linking procedures that may jeopardize the performance of microelectrode recordings and lead to falsely elevated responses in biological systems. In this study, the sensitivity of glutaraldehyde cross-linked glutamate oxidase-based microelectrode arrays to 22 amino acids was tested and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 68 publications
(86 reference statements)
2
39
0
Order By: Relevance
“…This length may determine the flexibility of the protein matrix and the degrees of freedom that proteins retain once they are immobilized, thereby affecting substrate specificity. Interestingly, when glutaraldehyde is preincubated in bovine serum albumin (BSA) prior to enzyme immobilization, these effects on substrate specificity are attenuated . It is possible that under these conditions, enzyme immobilization is achieved with glutaraldehyde molecules that are already bound to BSA, and this would provide a longer chain of cross‐linked molecules for immobilization.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This length may determine the flexibility of the protein matrix and the degrees of freedom that proteins retain once they are immobilized, thereby affecting substrate specificity. Interestingly, when glutaraldehyde is preincubated in bovine serum albumin (BSA) prior to enzyme immobilization, these effects on substrate specificity are attenuated . It is possible that under these conditions, enzyme immobilization is achieved with glutaraldehyde molecules that are already bound to BSA, and this would provide a longer chain of cross‐linked molecules for immobilization.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…). This recent convergence of results is probably related to technical improvements in microelectrode designs and enzyme immobilization procedures . The effect of neuronal firing on resting glutamate concentrations is also debated.…”
Section: Examples Of In Vivo Biosensor Monitoringmentioning
confidence: 99%
“…However, one recent report suggested that the high selectivity of GluOx may be altered when glutaraldehyde is used as the cross-linking agent and thereby resulting in an increase in perceived resting glutamate levels when using wire-type microelectrodes (Vasylieva et al, 2013). However, studies using ceramic-based MEAs support that GluOx is selective over other amino acids when using our coating protocol of entrapping GluOx in a glutaraldehyde cross-linked BSA matrix (Burmeister et al, 2013). For one, we only observed minimal responses to select amino acids with glutaraldehyde cross-linked glutamate oxidase-coated MEAs, and furthermore, functional glutamate MEA biosensors employed for in vivo experiments use multiple means to minimize the potential interference from electroactive molecules (e.g., exclusion layers and self-referencing subtraction).…”
Section: Resting Levels Of Glutamate In the Cns: Comparisons To Micromentioning
confidence: 83%
“…For example, first one uses a highly selective enzyme, like glutamate oxidase (GluOx) which is extremely selective for l-glutamate over other amino acids (Kusakabe et al, 1983). Then GluOx is entrapped in a protein matrix such as bovine serum albumin (BSA) that is cross-linked with glutaraldehyde to retain the high enzyme-selectivity and activity after immobilization onto the MEA surface ( (Burmeister et al, 2013) green area shown in Figure 5.2).…”
Section: Why Perform Self-referencing Recordings?mentioning
confidence: 99%
“…Glutaraldehyde is a crosslinking agent that causes changes in the properties of albumin. The color change seen in Figure 1 is attributed to the formation of the aldimine linkages [19][20][21] . The glutaraldehyde reacts predominantly with the BSA through the amino groups of lysine to form the intermolecular covalent bonds 14 .…”
Section: Discussionmentioning
confidence: 99%